2012
DOI: 10.1017/jfm.2012.318
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady force generation and vortex dynamics of pitching and plunging aerofoils

Abstract: Experimental studies of the flow topology, leading-edge vortex dynamics and unsteady force produced by pitching and plunging flat-plate aerofoils in forward flight at Reynolds numbers in the range 5000–20 000 are described. We consider the effects of varying frequency and plunge amplitude for the same effective angle-of-attack time history. The effective angle-of-attack history is a sinusoidal oscillation in the range $\ensuremath{-} 6$ to $2{2}^{\ensuremath{\circ} } $ with mean of ${8}^{\ensuremath{\circ} } $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(89 citation statements)
references
References 57 publications
(50 reference statements)
6
82
1
Order By: Relevance
“…Similar pitching experiments on a flat plate at a lower Reynolds number between Re 5 × 10 3 and 2 × 10 4 performed by Baik et al [16] showed that the instantaneous angle of attack and reduced frequency k determined flow evolution and that the LEV separation occurred later in the motion period, or at a higher angle of attack, with increased k, in agreement with the results of Rival et al [17]. They showed that leading-edge vortex circulation tended to increase linearly with the phase of the airfoil motion, with a faster growth corresponding to a lower reduced frequency k.…”
Section: Doi: 102514/1j054784supporting
confidence: 76%
See 1 more Smart Citation
“…Similar pitching experiments on a flat plate at a lower Reynolds number between Re 5 × 10 3 and 2 × 10 4 performed by Baik et al [16] showed that the instantaneous angle of attack and reduced frequency k determined flow evolution and that the LEV separation occurred later in the motion period, or at a higher angle of attack, with increased k, in agreement with the results of Rival et al [17]. They showed that leading-edge vortex circulation tended to increase linearly with the phase of the airfoil motion, with a faster growth corresponding to a lower reduced frequency k.…”
Section: Doi: 102514/1j054784supporting
confidence: 76%
“…On pitching and plunging flat plates, Baik et al [16] showed that, for k ≤ 0.5, the LEV circulation increased linearly up until vortex separation, corresponding to this optimal formation time, whereas at k > 0.5, the vortex was pinched off prematurely due to the reversal of the airfoil motion. In experiments measuring various plunging motions at k 0.2-0.33, Rival et al [17] also found that the formation of the leading-edge vortex agreed with this optimal vortex formation time and suggested that, if the stroke motion could be altered such that the LEV saturated at the peak of the motion, the unsteady lift from LEV formation and dynamic stall could be used most effectively.…”
Section: Doi: 102514/1j054784mentioning
confidence: 99%
“…Recent studies (Ol et al 2009;Baik et al 2012;Pitt Ford & Babinsky 2013) have shown that classical potential flow theory from Theodorsen (1935), von Kármán & Sears (1938 and…”
Section: Analytic Argumentsmentioning
confidence: 99%
“…With the introduction of non-zero angle of attack, the airfoil may generate both thrust and lift. Heaving and pitching airfoils have also been studied extensively [Anderson et al, 1998, Ramamurti and Sandberg, 2001, Read et al, 2003, Ashraf et al, 2011, Baik et al, 2012, Widmann and Tropea, 2015. Pitching modifies the flow around the airfoil and can, for some combinations of the motion parameters, increase the net value of thrust and the propulsive efficiency.…”
Section: Introductionmentioning
confidence: 99%